IMPLEMENTASI MODEL PEMBELAJARAN BERBASIS MASALAH DALAM MENULIS TEKS PERSUASI DI KELAS VIII B SMPN 18 TANJAB TIMUR - Harnisa Agusnia; Rustam Rustam; Kamarudin Kamarudin (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2023)
This study aims to describe the implementation of problem-based learning models in writing persuasive texts in class VIII B of SMP Negeri 18 Tanjab Timur. This research was conducted at East Tanjab 18 Public Middle School. The data sources in this study were Indonesian language teachers and eighth grade students. The approach used in this research is a qualitative approach with a descriptive research type. the data used in this study is the application of a problem-based learning model carried out by the teacher when teaching accompanied by photographs that support the acquisition of information for research purposes. data collection techniques in this study by means of observation, interviews and documentation. The results of this study indicate that the implementation of problem-based learning models in writing persuasive texts in class VIII of SMP Negeri 18 Tanjab Timur has been carried out with the final assignment in the form of writing persuasive texts whose theme is taken from problems that exist in the environment around students. on the implementation of the problem-based learning model on persuasive text material divided into two meetings. at the first meeting two steps of the problem-based learning model were carried out, namely the orientation of students on problems and organizing students to learn, at the second meeting three steps of the problem-based learning model were carried out, namely guiding group learning, presenting results, and evaluating the process. Based on the results of the research, it can be concluded that the implementation of the problem-based learning model in writing persuasive texts in class VIII SMP Negeri 18 Tanjab Timur as a whole is well implemented in accordance with the steps of the problem-based learning model proposed by Priyatni (2014: 114) and also according to the lesson plan made by the teacher.